Intestinal angiomatosis - Ituño, Carlos; Castiglioni, Juan C; Aliano, Alberto; Iraola, María L (Cirugía del Uruguay, 1973)
In two case of angiomatosis of the small intestine, a large number of abnormal lacuna-type vascular elements are found in the sub-mucosa. Possible etiopathogenic factors triggering the hemorrhage are considered.